Evaluation of the baseline carbon sequestration rates of Indo‐Pacific temperate and tropical seagrass meadow sediments. Issue 1 (21st September 2021) - Miyajima, Toshihiro; Hamaguchi, Masami; Hori, Masakazu
Abstract: Seagrass meadows have great capacity to sequester and store organic carbon (OC) in sediments for the long term and have been considered as a carbon dioxide sink for national greenhouse gas inventories in the Intergovernmental Panel on Climate Change Guidelines. Therefore, there is an urgent need to determine a reliable, well‐constrained estimate of the baseline long‐term OC sequestration (burial) rate in seagrass meadows, evaluate its spatial and temporal variability, and understand the mechanisms that control the variability. Here, we report data on OC stocks and long‐term sequestration rates for 14 selected sediment cores collected from temperate and tropical seagrass meadows and adjacent bare areas in Japan and Thailand. We also tested several different radiocarbon dating calibration methods to evaluate sedimentation rates and identified potential complicating factors. The estimated OC sequestration rate ranged from 3.7 to 161 kg C ha −1  year −1, which is generally lower and less variable than reported global representative values, presumably because of differences in the time scale considered. The OC sequestration rate for temperate seagrass meadows was correlated with the average specific surface area of sediment, implying that geophysical and hydrodynamic factors constrain the long‐term OC sequestration rate. The baseline OC sequestration rate may be better constrained by the method used here, focusing on time scales of centuries to millennia, while the evaluation of OC sequestration on shorter time scales may be more suitable for assessing the environmental additionality of climate mitigation efforts based on blue carbon manipulation. Abstract : Organic carbon sequestration rate in northwestern Pacific seagrass meadows is relatively lower than the world‐wide averages and is correlated to specific surface area of sediment, implying geophysical rather than biological control on the carbon sequestration ecosystem function.